Perencanaan Pembangkit Listrik Tenaga Surya Di Pos Pengamatan Gunung Soputan - Novi Gusti Pahiyanti; Sigit Sumakajati; Axl Brian Androcles Tangkilisan (KILAT, 2019)
This planning is carried out on the basis to meet the electricity needs that must continuously deliver electricity at the observation point of Mount Soputan, this is because electricity needs are very important in seeing the movement of the volcano. This plan with a planned load of 18.04 kWh. For such loading, 20 solar panels with 200 Wp capacity are used, and 2 solar panels controllers (SCC) are used, with each SCC used for 10 solar panels. As for the batteries used as many as 3 pieces with each battery having an energy of 2.4 kWh, then for the inverter using an inverter with a power of 2650 W.